Assessment of the Sanitary Quality of Fruit Juices Sold in Some Public Schools in the Agblangandan District in the Southern Part of Benin - AVOCEFOHOU, Sako Alphonse; BEHANZIN, GBÉSSOHÈLÈ JUSTIN; ELEGBEDE, Jacqueline Clarisse; YOUSSAO ABDOU KARIM, ALASSANE; TCHOGOU, Pascal; BOYA, Bawa; HOUNSOU, M. T. Francis; GBAGUIDI, AHOTONDJI BERTIN; AHYI, V.; Ahokpè, Mélanie; BABA-MOUSSA, LAMINE SAÏD; CHABI, Nicodeme (My University, 2022)
Fruit juices are one of the favorite drinks for children these days. As a result, its production must be organized in such a way as to ensure quality and guarantee the safety of consumers in general and schoolchildren in particular. The objective of this study is to analyze the health quality of bissap, lemon and pineapple juices sold in some public schools in the district of Agblangandan. For this, we collected from the vendors, 12 pineapple juice, 14 bissap juice and 8 lemon juice during the morning recess. Then, the microbiological and physico-chemical analyzes were carried out on the juices. The microbiological analyzes made it possible to identify the presence of total mesophilic flora (1.09.104 CFU/ml), total Coliforms (2.78.103 CFU/ml), Escherichia coli (4.44.102 CFU/ml), Enterococci (86.1 CFU/ml) and Clostridium (13.2 CFU/ml) in bissap juices. These same germs have been identified in lemon and pineapple juices with varying loads. As for the physico-chemical parameters, the results revealed a high rate of turbidity, conductivity, temperature and pH of the juices. Factors such as failure to master hygiene rules when bagging juices, non-compliance with hygiene rules during handling and storage and then inappropriate hygiene practices are origin of the contamination of these juices. It is therefore urgent to prioritize the hygiene and health of school children through awareness-raising, education and regular and rigorous health control of the juices sold by sworn agents.
Keywords: Juice; sanitary quality; hygiene; school; Agblangandan; Benin